Faktor-Faktor Yang Mempengaruhi Keputusan Orang Tua dalam Memilih Sekolah Pada Sekolah Tunas Harapan Mandiri Rantauprapat - Sriwulan, Dona Reni; Pristiyono, .; Simanjuntak, Daslan (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2024)
The purpose of this study was to determine the effect of psychological factors and social factors onchoice decisions and customer satisfaction. This research is quantitative research by emphasizingSystematic Literature Review. The sample amounted to 65 people who were parents/guardians ofelementary school students of Sekolah Tunas Harapan Mandiri. The results showed that the respondentprofile can be concluded that it qualifies as a purposive sampling sample where the criteria used areparents / guardians who choose elementary school education at Tunas Harapan Mandiri School.Psychological factors partially do not influence the decision to choose elementary school education atTunas Harapan Mandiri School. Social factors partially influence the decision to choose elementaryschool education at Tunas Harapan Mandiri School. Psychological factors and social factorssimultaneously influence the decision to choose elementary school education at Tunas Harapan MandiriSchool. For research, it is hoped that research development can be carried out by paying attention tothe scope of the sample and the development of independent variables